Nano Biotechnology, Usage, Application and Challenges in Microbiology (Mini Review) - Ewadh, Ruqaya Muther Jalil (International Journal of Scientific Research in Biological Sciences, 2024)
Nanotechnology is a broad scientific discipline that has permeated almost every branch of study. Nanotechnology has significant applications in various fields such as environment, agriculture, industry, and medicine. It is particularly valuable in the diagnosis and treatment of microbial illnesses caused by bacteria, fungus, and viruses. This article provides concise explanations regarding the utilization of nanotechnology in the food industry and provides a summary of the various applications of nanotechnology in the field of microbiology. The discussion revolved around the applications of nano-particles, such as their antibacterial activity, as well as the use of nano-sensors for detecting microbes. However, it is necessary to take some measures while utilizing nanotechnology applications in order to prevent any potential toxicological and adverse impacts on both human health and the environment.